Reference Services in the Libraries of the Republic of Cameroon: Current State, Problems and Prospects - J. Zemengue (Библиосфера, 2021)
The reference services in Cameroonian libraries are lagging in the exercise of their activities. Thus, this study raises the problem of the organization and functioning of reference services in the libraries of Cameroon. The purpose of the research is to provide an updated view of research issues in reference services in the libraries of the Republic of Cameroon. It outlines the definition of the notion «reference service»; opens his essence, characteristics, and content; reveals the current state of reference services for Cameroonian libraries and the main factors influencing the activities of reference services in libraries of Cameroon. The research defines the attributes of a reference librarian and proposes and defines several ways and trends for the future improvement of reference services in the libraries of Cameroon. As part of the research conducted, the following methods were used: observation and interviews carried out in Cameroon libraries. The results of this study would, no doubt, be of great benefit to all libraries in Cameroon and should ideally be completed by the Cameroonian reference services.